Planar surface parameterization and texture mapping - Sun, Qingshuan. (2009)
Surface parameterization has been a well researched topic in computer graphics, due to its importance in computer geometry processing, computer vision and visualization. This paper reports the author’s research on the parameterization of 3D triangular surface meshes. This paper includes two main sections, each covering a different step in the research. In the first place, it summarizes the building of a 3D triangular mesh viewer, which is to be used in the rest work of the research. Within the mesh viewer, the author will survey, implement and compare some various planar surface parameterization algorithms. Besides planar parameterization, there will also be a brief discussion about spherical parameterization.